MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN WORD SQUARE PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN MATERI ORGANISASI KELAS V SDN 066045 MEDAN HELVETIA TAHUN AJARAN 2018/2019 - Ginting, Elsa liyana; Lumban tobing, Panni Ance (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2019)
The problem in this study is the result of student learning in learning citizenship education is still low because the teacher uses the lecture method and emphasizes memorization and making notes, student activeness to ask and answer questions in KBM activities is still not optimal so students are less motivated to learn. This research is a classroom action research in class V even semester 066045 Medan Helvetia field in the 2018/2019 school year with a total of 28 students. The acquisition of the results of the first cycle need to follow up on the second cycle, so that significantly the learning outcomes of the second cycle in the meta subjects of citizenship education in organizational material using the word square model increased to 28 students who completed their learning outcomes with a percentage of 100% with an average value of 85.00 from the management of learning outcomes tests in the second cycle the percentage of students' mastery learning has met the target as determined by the percentage of mastery learning ideal of 75% of students who have achieved the KKM score of 75. Therefore, it can be concluded that learning activities using the word square learning model can improve student learning outcomes in fifth grade SD Negeri 066045 Medan Helvetia. on learning civic education, organizational material.